IbM SISTEM INFORMASI PUSKESMAS PEMBANTU DI WILAYAH PUSKEMAS LUBUK BUAYA PADANG [IbM INFORMATION SYSTEMS ASSOCIATE CLINICS IN THE REGION DOWN VERA PUSKEMAS PADANG] - Nurmi Nurmi; Thomson Mary; Erna Juita (Universitas Pelita Harapan, 2017)
Bungo acolytes Pairs of clinics and Padang Sarai average visitors per day, approximately 20-30 people from all types of immunization conducted each month. Both the clinics served respectively by 2 medical personnel, in charge of conducting immunization, treatment against the patient and make a report in priodik every month that are reported to the parent of clinics Down Vera. See the occurred situation of limited medical personnel because of the patient's medical treatment and serving and making a report. This has resulted in a report given to the parent of clinics are often late, so leadership received reports of discontent and lack of quality of service perceived by the community. Thus goals for improving the health of children is also not achieved, so there is nothing for kids healthy, intelligent and powerful will be difficult to obtain. To fix the issue, designed and created, applied and used application program information system-based database for the management of immunization. The methods used in the implementation and use of the application program information system namely immunization management application program installed on the laptop will be used by the Midwife clinics as administrator, and then stop the manual systems and use application program management of the immunization clinic services to enter data that is recorded on the books of registration and status of patients into a program application, the system will process and store data on immunization database. This application can do a search based on the number of patient data patient medical recam. The system aims to administer immunization, improve the quality of child health care in creating healthy Indonesia children, smart and strong especially at Bungo Acolytes Puskemas Pairs and clinics Maid field. Application programs can also help the activities of a midwife for the management of immunization data, generate reports, reports of patient registration patient examination, immunization and participant card status card to patient immunization, stored into the database, it can be given whenever required by the direction of clinics Down Vera with a quick, precise and accurate.